The Multiform Nineties : Taiwan's Art Branches Out. - Huang Hai-Ming; Lu, Victoria, Y.; Shih, Jui-Jen; Wang Chia Chi Jason (Taipei : Taipei Fine Arts Museum Taipei, 2005)
Yu Peng ; Wang Wen-Chih ; Wang Jun-Jieh ; Wang Te-Yu ; Chiang, Paul ; Chu Chia-Hua ; Wu Tien-chang ; Wu Ma-Li ; Lee, Ming-Tse ; Lee Jiun-Shyan ; Lin, Michael Ming-Hang ; Lin, Shu-Min ; Lin Chun-Ju ; Lin Ju ; Lin Hang-Wen ; Hou Chun-ming ; Hou Lulu Shun-Tzy ; Hung Tung-Lu ; Hong Mei-Ling ; Yao Jui-Chung ; Fang Marvin Minto ; Hsu Maggie Hsun-Wei ; Hsu Jui-Hsien ; Yuan Jai ; Yuan Goang-ming ; Kao Chung-li ; Mei Dean-E ; Tsong Pu ; Hsu Yu-Jen ; Kuo Chen-Chang ; Kuo Wei-Kuo ; Lien Chieng-Hsing ; Lien Te-Cheng ; Chen Chien-Pei ; Chen Chieh-Jen ; Chen Shun-Chu ; Chen Kai-Huang ; Chen Hui-Chiao ; Chen Long-Bin ; Lu Hsien-Ming ; Tao Ya-Lun ; Peng Hsien-Hsiang ; Yu Ben ; Huang Wen-Hao ; Huang Buh-Ching ; Tang Huang-Chen ; Huang Chih-Yang ; Huang Chin-Ho ; Hwang, Michell ; Yang, Emily S.C. ; Yang Mao-Lin ; Tong Yang-Tzu ; Tsai Ken ; Tsai Hai-Ru ; Cheng Tsai-Tung ; Cheng Chiung-Ming ; Lu Ming-Te ; Lai Jun T ; Hsueh Ava ; Shieh Juin ; Chien Fu -Ken ; Lo Sen-Hao ; Su Wang-Shen ; Ku Shih-Yung
Chronology of the 1990s p. 194-203
Engels
Taiwanees
boek
Keywords: jaren 90; Taiwan